2014
DOI: 10.1097/jom.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity by Occupation Among US Workers

Abstract: Objective To estimate the prevalence of obesity and the change of prevalence of obesity between 2004–2007 and 2008–20011 by occupation among US workers in the National Health Interview Survey. Methods Self-reported weight and height were collected and used to assess obesity (body mass index ≥ 30 kg/m2). Gender-, race/ethnicity-, and occupation-specific prevalence of obesity were calculated. Results Prevalence of obesity steadily increased from 2004 through 2008 across gender and race/ethnicity but leveled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 26 publications
7
83
1
3
Order By: Relevance
“…Conhecendo as dificuldades de se obterem as informações de peso e altura aferidos de toda a população, o uso de medidas autorreferidas é um instrumento fácil e de baixo custo, e vem http://dx.doi.org/10.1590/1678-98652016000300005 sendo empregado em diversos inquéritos nacionais de saúde no mundo para avaliar o estado nutricional de populações [6][7][8][9] . Essas informações podem ser obtidas através de entrevistas pessoais ou por telefone e por questionários autoaplicáveis enviados pelo correio 10 .…”
Section: N T R O D U ç ã Ounclassified
“…Conhecendo as dificuldades de se obterem as informações de peso e altura aferidos de toda a população, o uso de medidas autorreferidas é um instrumento fácil e de baixo custo, e vem http://dx.doi.org/10.1590/1678-98652016000300005 sendo empregado em diversos inquéritos nacionais de saúde no mundo para avaliar o estado nutricional de populações [6][7][8][9] . Essas informações podem ser obtidas através de entrevistas pessoais ou por telefone e por questionários autoaplicáveis enviados pelo correio 10 .…”
Section: N T R O D U ç ã Ounclassified
“…They found that white collar workers had a significant increase in obesity rates between 2004-2007 and 2008-2011 while blue collar workers did not 49 . Since obesity is becoming more prevalent in white collar workers as compared to blue collar workers, it is important to examine cardiovascular disease risk even more in white collar workers to develop plans to help them reduce this risk.…”
Section: Work Placementioning
confidence: 99%
“…They found that 16.8% of male employees measured who were employed as postsecondary educators were classified as obese 49 . This is 5% less than what we saw in our sample, however this is most likely due to small sample size.…”
Section: Body Mass Indexmentioning
confidence: 99%
See 2 more Smart Citations